Diagnosis dan tatalaksana Sindroma Stevens-Johnson (SJS) pada anak: tinjauan pustaka - Komang Ayu Witarini (DiscoverSys Inc., 2019)
Background: Stevens-Johnson Syndrome (SJS) is an emergency situation with a fairly high mortality rate characterized by a triad of lesions on the skin, mucosa orifice, and eyes. In general, SJS is caused by a reaction to a drug. This literature review is trying to explain more in the effort to diagnose and manage SJS specifically in children.Methods: This literature review involved 14 relevant literature from 1990-2011 about SJS. Different data sources or manual literature search methods used to find articles related to the topic of literature.Results: The diagnosis of SJS is mainly based on clinical symptoms. The clinical picture of SJS is known to be very similar to Toxic Epidermolysis Necrotikans (TEN). Various efforts to stop all drugs given previously is the main treatment, supported by supportive treatment of accompanying symptoms. The mortality rate depends on the presence of severe complications and delay of treatment.Conclusion: Early diagnosis and prompt treatment are the key to the management of SJS in children.